Medical Ethics and Human Rights in Reproductive Health - Muhunthan, K; Arulkumaran, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
DOI: http://dx.doi.org/10.3126/njog.v9i1.11177 NJOG 2014 Jan-Jun; 2(1):5-7